Do pyrene and Kandelia obovata improve removal of BDE-209 in mangrove soils?. (February 2020) - Li, Ruili; Ding, Huan; Guo, Meixian; Shen, Xiaoxue; Zan, Qijie
Abstract: Combined pollution caused by polybrominated diphenyl ethers (PBDEs) and polycyclic aromatic hydrocarbons (PAHs) in mangrove wetlands is serious, with their remediation to be been paid more and more attention. However, little is known about the combined impact of PAHs and mangrove species on removal of PBDEs in contaminated soils. In this study, BDE-209 and pyrene were selected and a 9 months experiment was conducted to explore how BDE-209 removal in contaminated soil varied with pyrene addition and Kandelia obovata planting, and to clarify corresponding microbial responses. Results showed that BDE-209 removals in soil induced by pyrene addition or K. obovata planting were significant and stable after 6 months, with the lowest levels of BDE-209 in combined pyrene addition with K. obovata planting. Unexpected, root uptake of BDE-209 in K. obovata was limited for BDE-209 removal in soil, which was verified by lower total amount of BDE-209 bioaccumulated in K. obovata 's root. In soil without K. obovata planting, BDE-209 removal caused by pyrene addition coexisted with changed bacterial abundance at phylum Planctomycetes and Chloroflexi, class Planctomycetacia, and genus Blastopirellula . K. obovata -induced removal of BDE-209 in soil may be related to bacterial enrichment in phylum Proteobacteria, class Gammaproteobacteria and genus Ilumatobacter, Gaiella . Thus, in BDE-209 contaminated soil, microbial community responses induced by pyrene addition and K. obovata planting were different at phylum, class and genus levels. This is the first study demonstrating that pyrene addition and K. obovata planting could improve BDE-209 removal, and differently affected the corresponding responses of microbial communities. Graphical abstract: Image 1 Highlights: BDE-209 uptake and debromination in K. obovata root is limited in affecting soil BDE-209 removal. Pyrene addition improved removal of BDE-209 in contaminated soil without K. obovata planting. K. obovata planting improved removal of BDE-209 in contaminated soil with/without pyrene addition. Microbial community responses for BDE-209 removal caused by pyrene and K. obovata were different.